God (≡ Elohim), The First Small World Network - Ausloos, Marcel (Frontiers in Physics, 2022)
In this paper, the approach of network mapping of words in literary texts is extended to ''textual factors'': the network nodes are defined as ''concepts''; the links are ''community connexions''. Thereafter, the text network properties are investigated along modern statistical physics approaches of networks, thereby relating network topology and algebraic properties, to literary texts contents. As a practical illustration, the first chapter of the Genesis in the Bible is mapped into10 node network, as in the kabbalah approach, mentioning God (Elohim). The characteristics a of the network are studied starting from its adjacency matrix, and the corresponding Laplacian matrix. Triplets of nodes are particularly examined in order to emphasize the ''textual (community) connexions'' of each agent "emanation", through the so called clustering coefficients and the overlap index, whence measuring the ''semantic flow'' between the different nodes. It is concluded that this graph is a small-world network, weakly disassortative, because its average local clustering coefficient is significantly higher than a random graph constructed on the same vertex set.